Studi Literatur: Adab Menuntut Ilmu Dalam Perspektif Kitab KH.Hasyim Asy’ari dan Naquib Al-Attas di Era Digital - Saiddaeni Saiddaeni; Enggal Bagas Nova Saputra; Muhammad Amiruddin Dardiri; Achfan Aziz Zulfandika (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2023)
The problem in this day and age is that technology is increasingly sophisticated and has changed the way humans obtain information. The presence of devices such as smartphones, tablets and computers has enabled us to access information easily, anywhere and anytime. So students can learn anywhere without the presence of a teacher. It is important to remember that the role of teachers in education is still very important. Teachers not only provide knowledge, but also guide and help students in understanding and applying the information they get. In studying, manners or morals have a very important role. In fact, adab is considered more important than knowledge itself. This article uses literature study by searching for information with the keywords adab, science and Islam. So that answers can be found regarding the manners of a student and teacher in the teaching and learning process. Searching with these keywords provides an in-depth understanding of how adab plays a key role in the relationship between a student and teacher in the teaching and learning process in the Islamic tradition. The results obtained are that the manners of knowledge through the books of previous scholars are very valuable, such asAdabul 'Alim wal Muta'allimwork K.H. Hasyim Asy'ari and Thoughts of Syed Muhammad Naquib Al-Attas . The book helps seekers of knowledge, especially Muslims, to follow the guidelines that have been passed down by previous scholars in their efforts to pursue knowledge. By understanding and respecting these manners, one can ensure that their learning journey not only brings knowledge, but also forms good character and morals.